Pengaruh Penerapan E-system Perpajakan, Kualitas Pelayanan, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak : (Studi pada KPP Pratama Bekasi Barat) - Anisa Ayu Safitri; Neneng Lasmita Susanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2026)
This study aims to analyze the impact of the implementation of the e-tax system, quality of tax services, and tax sanctions on the compliance of individual taxpayers. This study uses primary data obtained by distributing questionnaires to individual taxpayers who are users of e-Registration, e-Filing, and e-Billing registered at the Bekasi Barat Tax Office (KPP). The sampling technique used in this study is Convenience Sampling with a total of 115 respondents. This study uses a quantitative approach with Multiple Linear Regression Analysis and IBM SPSS Statistics 26 as a tool. The test results show that the implementation of the e-tax system and tax penalties has a significant effect on taxpayer compliance, while the quality of tax services does not have a significant effect on taxpayer compliance.